Comparison and evaluation of conventional RT-PCR, SYBR green I and TaqMan real-time RT-PCR assays for the detection of porcine epidemic diarrhea virus. (June 2017) - Zhou, Xinrong; Zhang, Tiansheng; Song, Deping; Huang, Tao; Peng, Qi; Chen, Yanjun; Li, Anqi; Zhang, Fanfan; Wu, Qiong; Ye, Yu; Tang, Yuxin
Abstract: Porcine epidemic diarrhea (PED) caused by porcine epidemic diarrhea virus (PEDV) is a highly contagious intestinal disease, resulting in substantial economic losses to the swine industry worldwide. In this study, three assays, namely a conventional reverse transcription-polymerase chain reaction (RT-PCR), a SYBR Green I real-time RT-PCR and a TaqMan real-time RT-PCR targeting the highly conserved M gene of PEDV, were developed and evaluated. Then, the analytical specificity, sensitivity and reproducibility of these assays were determined and compared. The TaqMan real-time RT-PCR was 100-fold and 10, 000-fold more sensitive than that of the SYBR Green I real-time RT-PCR and the conventional RT-PCR, respectively. The analytical sensitivity of TaqMan real-time RT-PCR was 10 copies/μl of target gene and no cross amplification with other viruses tested was observed. With the features of high specificity, sensitivity, and reproducibility, the TaqMan real-time RT-PCR established in this study could be a useful tool for clinical diagnosis, epidemiological surveys and outbreak investigations of PED. Highlights: An endpoint RT-PCR, a SYBR Green I qRT-PCR and a TaqMan qRT-PCR for the detection of PEDV were established and evaluated. TaqMan qRT-PCR was 100- and 10, 000-fold more sensitive than the SYBR Green I qRT-PCR and the endpoint RT-PCR, respectively. With high specificity, sensitivity and reproducibility, the TaqMan qRT-PCR could be a useful tool for the detection of PEDV.